Removal of Organic Impurities from Water Using a Reactor with Photoactive Refill - Joanna Grzechulska-Damszel (International Journal of Photoenergy)
The aim of the presented work was the removal of phenol from water using a reactor with photoactive refill. Titanium dioxide (Chemical Factory “Police” Poland) was immobilized on the base material as a thin layer from the alcoholic suspension followed by thermal stabilization. The glass fabric was applied as a support for the titania coating. The results of studies revealed that the titania coatings show a high photocatalytic activity toward the phenol decomposition in water. The complete removal of phenol was achieved in the relatively short time of 23 hours. The prepared coatings exhibit high stability in repeated cycles of water treatment. The proposed reactor with photoactive refill solves the problem of necessity of replacement of the reactor or the parts of the reactor when the photocatalysts activity decreases. In the case of activity drop of the photocatalyst, only the photoactive refill can be easily replaced.